The Effect of Familiar Songs’ Tune to Improve Students’ Understanding in Irregular Verbs - Tirza A. Kumayas (Journal of International Conference Proceedings (JICP), 2020)
English is one of the most important language in the world. It can be used as a language in any part of the world. That is why it is taught at all level of education in our country, Indonesia. Elementary school, high school and university students are all learning English now. However, learning English sentence pattern is much more difficult than learning Indonesian’s. English language learners usually get problems in understanding and using those three forms of verb which are commonly called irregular verbs as the core of tenses which are very essential in formulating tenses, have been taught at Junior and Senior High School. However, it is assumed that they are hardly used, even by those students of English Department of FBS UNIMA in Tondano. As prove it is observed that almost all students rarely speak English although they always meet at campus it is seems that they do not know how to speak English even a very simple sentence. It is assumed that their low of English competence has made them not have confidence to do their performance. Anyway, this is still an assumption that needs to be investigated. The low of competence of English knowledge might have been one of the causes that make them not able to communicate in English. Not mastering the three forms of verbs, their meanings and functions caused them enable to expressed what happened in the past present and future or they might know the structure or the pattern but do not know when to use. The research questions: Can the effect of familiar songs’ tune improve students’ understanding on irregular verbs. The study was delimited to the forms, meanings and functions of irregular verbs. The focus on this study was the fourth semester students of English department, FBS UNIMA. The tune is limited to that belongs to the songs which are well known by the students. To learn and memorize irregular verbs which have the same V2 and V3, the tune is taken from the song “Are you sleeping Brother John”. Each line was sung twice in order that the students are able to memorize easily. This is a quantitative research through pre-experimental design with one group pre-test and post-test design. The pretest was given to the students before treatment and the post-test was given after the treatment. This research showed that the effect of Familiar Songs’ Tune was improved students’ understanding on irregular verbs and it has made the class atmosphere become so lively and the students enjoy learning English by singing. Learning English by singing is fun.